The Oxford handbook of family policy: a life-course perspective - Daly, Mary; Pfau-Effinger, Birgit; Gilbert, Neil; Besharov, Douglas J. (Oxford handbooks, 2023)
Drawing on a multidisciplinary group of experts from many countries, this handbook is intended to be a reference work that provides students and scholars in policy-related disciplines a wide-ranging perspective on the diverse ways that family policies respond to modern issues and trends over the life course.